Membangun Pesantren Personal: Regulasi Diri Santri Tuna Netra dalam Menghafal Al-Qur'an Pasca Lulus dari Pesantren - Riza Kurniawan (Yayasan Al-Afif, 2026)
This study explores the self-regulation dynamics of visually impaired pesantren alumni in maintaining Quranic memorization during their transition to society. Using a qualitative phenomenological approach with four informants, the research identifies that the loss of institutional support structures poses a significant challenge to consistency. Results reveal a spiritual coping mechanism where blindness is perceived as a protective shield against sin, bolstering intrinsic motivation. The key finding highlights the